2020
DOI: 10.1021/acs.inorgchem.0c02052
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Factors That Influence the Deoxygenation of Oxyanions in Atomically Precise, Oxygen-Deficient Vanadium Oxide Assemblies

Abstract: Here, we report our findings related to the structural and electronic considerations that influence the rate of oxygen-atom transfer (OAT) to oxygen-deficient polyoxovanadate alkoxide (POV-alkoxide) clusters ([V6O6(OC2H5)12] n ; n = 1–, 0, 1+). A comparison of the reaction times required for the reduction of nitrogen-containing oxyanions (NO x –, x = 2, 3) by the POV-ethoxide cluster in its anionic (1-V 6 O 6 1– ; VIIIVIV 5), neutral (4-V 6 O 6 0 ; VIIIVIV 4VV), or cationic (6-V 6 O 6 1+ ; VIII… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…22 This attribute has translated to their use as molecular models for the surface reactivity of their nanoscale congeners. [23][24][25] With interest in elucidating the consequences of surface ligation, researchers have developed synthetic methods in order to establish organic-inorganic POM hybrid systems. [26][27][28] In a similar fashion to strategies invoked for ligation of metal oxide nanoparticles, an organic functional group is grafted to the surface of a POM through carboxylate, phosphonate, siloxide or alkoxide linkages.…”
Section: Introductionmentioning
confidence: 99%
“…22 This attribute has translated to their use as molecular models for the surface reactivity of their nanoscale congeners. [23][24][25] With interest in elucidating the consequences of surface ligation, researchers have developed synthetic methods in order to establish organic-inorganic POM hybrid systems. [26][27][28] In a similar fashion to strategies invoked for ligation of metal oxide nanoparticles, an organic functional group is grafted to the surface of a POM through carboxylate, phosphonate, siloxide or alkoxide linkages.…”
Section: Introductionmentioning
confidence: 99%
“…Toward this goal, the electronic properties of calixV 6 O 6 –1 were interrogated via infrared (IR) and electronic absorption spectroscopies (Table , Figures and ). These two techniques, taken in tandem, have been demonstrated to report on the degree of reduction of the cluster core. ,,, IR analysis of calixV 6 O 6 –1 reveals transitions at 1051 and 960 cm –1 , assigned to ν­(O b –Me) and ν­(VO t ), respectively (Table , Figure ). These values are shifted from those reported for V 6 O 6 –1 (ν­(O b –Me) = 1047 cm –1 ; ν­(VO t ) = 951 cm –1 ) and exhibit significant shouldering, likely due to the incorporation of the calix ligand at the surface of the assembly.…”
Section: Resultsmentioning
confidence: 99%
“…Isolation of this oxygen-deficient vanadium oxide assembly on preparative scales allows for defect formation and subsequent reactivity to be probed separately. Toward this goal, our laboratory has investigated the reactivity of these oxygen-deficient assemblies; we reported activation of nitrite and nitrate by V 6 O 6 –1 , whereby oxygen atom transfer to the surface of the cluster from the oxyanion results in the formation of NO. , We have also described the reactivity of the oxygen-deficient POV-alkoxide with O 2 ; exposure of V 6 O 6 –1 to O 2 afforded quantitative formation of the fully oxygenated parent cluster, V 6 O 7 –1 . In the latter study, we proposed that O 2 activation by V 6 O 6 –1 proceeds via a multicluster substrate activation pathway; two vanadium­(III) centers bind to opposite ends of O 2 , each providing two reducing equivalents for the complete cleavage of the OO bond.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…[78] More recently, Matson and colleagues have used vanadium oxo-alkoxide clusters of the general formula [V 6 O 7 (OR) 12 ] n± (R = organic group, e.g., CH 3 ) as molecular models to understand the redox-chemistry and surface oxygen removal of these systems (Figure 7). [79][80][81] The group showed that terminal VO bonds in these clusters can be selectively activated by oxygen atom transfer using oxophilic O-acceptors. In consequence, removal of an oxygen atom from a {V V O} species results in formation of a two-electron reduced {V III } surface site, [79] similar to the Mars-van Krevelen process proposed for solid-state vanadium oxides.…”
Section: Pom-sacs As Models For Reducible Solid-state Metal Oxidesmentioning
confidence: 99%